Energy and Frequency Characteristics of Microseismic Particles in a Complex Geological Model. Issue 12 (11th October 2022) - Zhou, Linli; Jia, Baoxin; Zheng, Kenan; Chen, Hao; Zhao, Long
Abstract: This study aims to better understand the energy–frequency characteristics of microseismic wave propagation by monitoring particles in complex geology. Artificial seismic source experiments are conducted using a complex geological model, and variational mode decomposition method is applied to process the microseismic signals, obtain reconstructed microseismic signals and decomposition modes, and calculate the microseismic particle input energy and signal energy at each measurement point. Computations derived from the Sadoff empirical formula are used to evaluate the attenuation of the microseismic particle input energy with the propagation distance. The relationships between microseismic wave center frequency and energy and between the microseismic particle input energy and microseismic signal energy are elucidated. The results show that the microseismic particle input energy follows a power exponential decay trend with increasing propagation distance; the values and distributions of the microseismic particle input energy and signal energy conform to a Gaussian trend in the frequency domain; various geological structures and combinations thereof impose frequency modulation effects on the microseismic wave, where the frequency modulation interval depends on the microseismic waves across the different interfaces; and the linear slope describing the relationship between microseismic particle input energy and signal energy can reflect the microseismic wave propagation state. Abstract : The microseismic energy and frequency relationship and the particle input energy and signal energy relationship are established. The frequency modulation effect at the geotechnical medium interface is found, and the microseismic wave propagation state can be reflected by the peak center frequency of the energy–frequency relationship and the linear slope of the energy–energy relationship.